Pelestarian Keanekaragaman Hayati Flora Melalui Wisata Edukasi Untuk Pembelajaran IPA Bagi Calon Guru MI di Banjarmasin - J, Jumiati; Arifa, Tutus Rani; A, Abdurrahim (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This dedication program aims to enhance the awareness and competence of prospective Madrasah Ibtidaiyah (MI) teachers in conserving flora biodiversity through educational tourism approach as a science learning medium. Activities were implemented in the Banjarbaru City Botanic Garden, which is a natural laboratory rich in local and endemic flora, with an integrative approach including material delivery, field observation, as well as competency evaluation. Participants consisted of prospective students of MI teachers who were mentored to identify plants, understand ecosystems, and integrate local wisdom-based environmental conservation values. The methods employed create engaging, in-depth, and sustained learning experiences. Results showed a significant improvement in the participants’ ability in composing science learning activities that were contextual, innovative, and based on scientific observation. Additionally, participants showed positive attitudes towards environmental sustainability and high enthusiasm for implementing this learning model in their future school. These activities not only impact on improving pedagogical competencies, but also form caring teachers and become agents of change in preserving biodiversity in primary education environments. This model can serve as a reference for other community engagements focused on conservation and first-hand experience-based science learning.